Genetic epidemiology of susceptibility to malaria: not only academic exercises. - Verra, F; Avellino, P; Bancone, G; Mangano, V; Modiano, D (2008)
Descriptive genetic epidemiology represents the initial step of a logical procedure of linked and consequential phases spanning from the identification of genes involved in the resistance/susceptibility to diseases, to the determination of the underlying mechanisms and finally to the possible translation of the acquired knowledge in new control tools. In malaria, the rational development and potential of this pathway is based on complementary interactions of heterogeneus disciplines going from epidemiology (the transmission, the infection, the disease) to vaccinology passing through genetics, pathogenesis, and immunology. Several epidemiological approaches can be applied in the study of the genetic susceptibility to Plasmodium falciparum malaria: intra-ethnic case-control studies comparing genetic candidates of resistance/susceptibility between subjects with different presentation of malaria (from severe disease to asymptomatic infection) and the general healthy population is the classic approach; inter-ethnic comparative analyses among populations with different genetic backgrounds, exposed to the same epidemiological context and showing different susceptibility to the disease is a further, complementary, strategy.